The influence of plural dominance in aphasic word production - Biedermann, Britta-Andrea; Lorenz, A.; Beyersmann, E.; Nickels, L. (2012)
Background: Plural dominance refers to the relative difference between the frequencies of a word in its singular and plural forms. Most of the evidence for theoretical accounts of plural dominance has come from psycholinguistic perception experiments (e.g., Baayen, Burani, & Schreuder, 1996; Baayen, Dijkstra, & Schreuder, 1997; Baayen, Schreuder, & Sproat, 1998). Only a few studies have investigated the production side of dominance, even in unimpaired speakers (e.g., Baayen, Levelt, Schreuder, & Ernestus, 2008). To our knowledge there is only one published neuropsychological study from Luzzatti, Mondini, and Semenza (2001) that uses reading-aloud data from an Italian brain-impaired speaker. Although findings across paradigms are inconsistent, they do indicate that plural-dominant nouns behave differently from singular-dominant nouns, and therefore suggest a difference in representation.Aims: This paper investigates processing of plural nouns in aphasia with a specific focus on effects of dominance.Methods & Procedures: We carried out two single-case studies with two women with aphasia, FME and DRS, who showed word retrieval deficits in picture naming as a result of different underlying functional impairments. The main task of interest was picture naming of single and multiple objects in order to test effects of plural dominance. In addition, word-picture matching tested number representation in comprehension.Outcome & Results: DRS showed a specific morphological impairment with plural marking, whereas FME had no specific morphological deficit. The results are discussed in the framework of current psycholinguistic accounts on the representation and processing of plural nouns (e.g., Levelt, Roelofs, & Meyer, 1999; Schreuder & Baayen, 1995).Conclusions: Different effects of plural dominance shown by both women with aphasia result from different underlying functional deficits, which indicate differences in the representation of plural dominance across processing levels. © 2012 Copyright 2012 Psychology Press, an imprint of the Taylor & Francis Group, an Informa business.